"The Neolithic Settlement of Aknashen (Ararat valley, Armenia)" - Badalyan , Ruben (Archaeopress Publishing, 2022)
The Neolithic settlement of Aknashen (Ararat valley, Armenia): excavation seasons 2004-2015 is the first monograph devoted to the Neolithic period in Armenia. The research is based on an Armenian-French project, in which specialists from Canada, Romania, Germany and Greece also participated. The volume concerns the natural environment, material culture and subsistence economy of the populations of the first half of the 6th millennium BC, who established the first sedentary settlements in the alluvial plain of the Araxes river. The thickness of the cultural layer of Aknashen (almost 5m), the extent of the excavated areas and the multidisciplinary nature of the research, confer great importance upon this site for the study of the Neolithic, both in Armenia and in the South Caucasus as a whole. The publication examines the similarities and differences that exist between the sites established in the 6th millennium in the basins of the rivers Araxes (Armenia) and Kura (Georgia and Azerbaijan), as well as parallels with contemporary cultures in Southwest Asia. It also examines questions concerning the characterisation and periodisation of the Neolithic in the central part of the South Caucasus, the emergence of a production economy (pottery, animal husbandry, etc.) and the Neolithisation of this region.